Antidiabetic Activity Of Annona squamosa L In Experimental Induced Diabetic Rats - Tomar, Ranveer S (International Journal of Pharmaceutical & Biological Archive, 2013)
Antidiabetic Activity Of Annona squamosa L In Experimental Induced Diabetic Rats